Padrões de diversidade e composição funcional de espécies arbóreas no Cerrado: o papel do clima, fogo e adensamento arbóreo - Nascimento, Diego Raymundo (2021)
The process of woody plant encroachment has been associated with changes in the ecosystem functions of savannas, either increasing carbon stock or causing losses in biodiversity. This thesis aimed to understand how the process of woody plant encroachment may be related to the structure, diversity and functional characteristics of the Cerrado sentido restrito plant community. Thus, each of the three chapters presented had a main question: 1) How does woody plant encroachment affects the floristic and functional characteristics of adult and regenerating tree individuals in a typical Cerrado? 2) How does the diversity of species, and the floristic and functional composition change over time in an area that are under woody plant encroachment? 3) How do woody plant encroachment, climatic factors and fire influence the species diversity and functional composition of tree communities in large-scale in the Cerrado? In the first chapter, our study showed that in a Cerrado sentido restrito that is under the process of woody plant encroachment, young and adult trees are not floristically similar. In addition, young individuals showed higher species richness, and a higher proportion of species with thin bark and seeds dispersed by the animals. In the second chapter, our results showed that species life history strategies are changing through an increase in species dominance with an acquisitive resource use strategy (faster resource acquisition and faster growth rates). In the third chapter, our results indicated that in the climate change scenario, an increase in temperature and a decrease in rainfall can cause a decline in species diversity and a change in functional composition through a decrease in the abundance of both specialist forest and savanna specialist species, favoring species with life strategies that allow persistence in warmer temperatures (as well as species with high SLA and wood density). In addition to and partially caused by climate change, we also demonstrated that woody plant encroachment can cause a decline in biodiversity and favor species with strategies adapted to the high productivity of the ecosystem even considering only arboreal species. In addition, fire had no effect on biodiversity or functional composition.